2012
DOI: 10.1155/2012/687510
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Endometrial Stromal Sarcoma with Synchronous Bilateral Adenocarcinoma of Ovary

Abstract: Endometrial stromal tumor is a rare mesenchymal uterine tumor. We report the case of a patient with endometrial stromal sarcoma and concomitant bilateral endometrioid adenocarcinoma of the ovary in the context of pelvic endometriosis. The patient underwent a complete cytoreduction including total hysterectomy and bilateral adnexectomy, pelvic lymphadenectomy, appendicectomy, infracolic omentectomy, and pelvic peritonectomy. This is the first report to our knowledge that describes a synchronous endometrial stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Based on our experience and a review of the available literature, surgical resection is the mainstay of treatment for primary ovarian ESS. Primary surgery for early disease includes hysterectomy and bilateral salpingo-oophorectomy; tumor debulking is reserved for advanced-stage disease [ 1 , 11 , 20 ]. Lymph node metastasis can occur in uterine endometrial stromal sarcomas at a rate of 2% to 45%; however, lymphadenectomy does not seem to improve survival [ 26 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our experience and a review of the available literature, surgical resection is the mainstay of treatment for primary ovarian ESS. Primary surgery for early disease includes hysterectomy and bilateral salpingo-oophorectomy; tumor debulking is reserved for advanced-stage disease [ 1 , 11 , 20 ]. Lymph node metastasis can occur in uterine endometrial stromal sarcomas at a rate of 2% to 45%; however, lymphadenectomy does not seem to improve survival [ 26 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the treatment for the comparable uterine tumors, adjuvant therapies including radiotherapy, chemotherapy, and hormonal therapy have been used for the management of primary ovarian ESS [ 1 , 4 , 6 , 11 , 20 ]. Low-grade ESS is considered a hormone-dependent malignancy, which means hormonal therapy with high-dose oral progestins, gonadotropin-releasing hormone analogs, and aromatase inhibitors may be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Gene sequencing has shown that approximately 20% of ovarian endometriosis (OE) and deep endometriosis lesions have cancerous somatic driver mutations [17]. Cancer arising with A is very rare, with transformation occurring in only 1% of cases [18][19][20]. The first case of clear cell adenocarcinoma (CACC) and endometrioid carcinoma (EC) resulting from A was reported in 1897 [21].…”
Section: Morphological Characteristics Of Endometriosis and Adenomyosismentioning
confidence: 99%
“…This pathology is rare, with a 1% incidence of cases associated with malignant transformation reported in the literature [18][19][20]. The incidence of these transformations could be influenced by the missing histopathological examination of the whole tumor detected.…”
Section: Microscopic Characteristics Of a And E Local And Glandular F...mentioning
confidence: 99%
“…Cancer arising from adenomyosis is very rare, with transformation occurring in only 1% of cases [4,5,9] and in older individuals [10]. The first case of clear cell and endometrioid carcinoma arising from adenomyosis was described in 1897 [3].…”
Section: Introductionmentioning
confidence: 99%